Social Work’s Role in Promoting Participation for Children and Youth with Mental Health-Related Disabilities in the German Child and Youth Welfare System - Christopher Romanowski-Kirchner (Journal of Comparative Social Work, 2026)
This article offers a theory- and legally informed conceptual analysis of interprofessional collaboration between youth welfare and child and adolescent psychiatry, with a focus on the legal construct of seelische Behinderung (mental health-related disability) in German child and youth welfare services (section 35a of the Social Code Book VIII). The ‘integration assistance for children and adolescents with mental health-related disabilities’ is a specific social work service within the German child and youth welfare system. It complements psychiatric and psychotherapeutic interventions by providing social-ecological forms of support aimed at promoting social participation. The central questions are: How is inclusion support for children and adolescents with so-called mental health-related disabilities actually practiced in the German system, and to what extent does this practice reflect a professional social work perspective? The theoretical framework combines the WHO’s concept of disability and the social work-based theory of integration and life conduct with the legal concept of integration assistance. As supporting evidence, the analysis draws on the small body of published research in this field of practice, including user-centered case reconstructions based on biographically grounded problem-centered interviews with former service users, and studies on interprofessional collaboration at the youth welfare–child and adolescent psychiatry interface. Findings reveal a persistent gap in how social workers in child and youth services assert their unique contributions in complex support contexts. Although a social work mandate is clearly embedded in integration assistance for young people with mental health-related disabilities, it is often not recognized as such or effectively implemented in practice. The article argues that these difficulties reflect not only structural constraints but also contested professional jurisdictions and recognition struggles at the youth welfare–child and adolescent psychiatry interface.